Análise de superfícies seletivas de freqüência para aplicações em ondas milimétricas - Medeiros, Gilcarlos Ribeiro de (2001)
This work consists in the development of a theoretical and numerical analysis for frequency selective surfaces (FSS) structures with conducting patch elements, such as rectangular patches, thin dipoles and cross dipoles, on anisotropic dielectric substrates. The analysis is developed for millimeter wave band applications. The analytical formulation is developed in the spectral domain, by using a rigorous technique known as equivalent transmission line method, or immitance approach. The numerical analysis is completed through the use of the Galerkin's technique in the Fourier transform domain, using entire-domain basis functions. In the last decades, several sophisticated analytical techniques have been developed for FSS structure applications. Within these applications, it can be emphasized the use of FSS structures on reflecting antennas and bandpass radomes. In the analysis, the scattered fields of the FSS geometry are related to the surface induced currents on the conducting patches. After the formulation of the scattering problem, the numerical solution is obtained by using the moment method. The choice of the basis functions plays a very important role in the numerical efficiency of the numerical method, once they should provide a very good approximation to the real current distributions on the FSS analyzed structure. Thereafter, the dyadic Green's function components are obtained in order to evaluate the basis functions unknown coefficients. To accomplish that, the Galerkin's numerical technique is used. Completing the formulation, the incident fields are determined through the incident potential, and as a consequence the FSS transmission and reflection characteristics are determined, as function of the resonant frequency and structural parameters. The main objective of this work was to analyze FSS structures with conducting patch elements, such as thin dipoles, cross dipoles and rectangular patches, on anisotropic dielectric substrates, for high frequency applications. Therefore, numerical results for the FSS structure main characteristics were obtained in the millimeter wave bando Some of these FSS characteristics are the resonant